The influence of yttria-stabilised zirconia and cerium oxide on the microstructural morphology and properties of a mica glass-ceramic for restorative dental materials. Issue 3 (3rd July 2021) - Srichumpong, Thapanee; Pintasiri, Suphahud; Heness, Greg; Leonelli, Cristina; Meechoowas, Ekarat; Thongpun, Noparat; Teanchai, Chayada; Suputtamongkol, Kallaya; Chaysuwan, Duangrudee
ABSTRACT: The addition of yttria-stabilized zirconia and cerium oxide to this mica glass ceramic was found to increase mechanical properties and decrease chemical solubility. They were also found to be able to control translucency. X-ray diffraction showed no significant change in phase formation with phlogopite-Ca mica, fluorapatite and tetragonal zirconia the main phases present with their addition. Scanning electron microscopy showed that the additives did affect the grain morphology significantly and this was the controlling factor in the observed changes in strength, hardness, and solubility. The microstructures consisted of mainly plate-like and interlocking crystals. The largest increased in strength and hardness and the largest decreased in chemical solubility can be attributed to the largest change in grain morphology by the addition of both the YSZ and CeO2 . The values of hardness, biaxial flexural strength and chemical solubility were 3.5–6.2 GPa, 105–120 MPa and 142–732 µg/cm 2, respectively making them acceptable for dental materials according to ISO 6872:2015. The addition of YSZ increased the opacity, whilst the CeO2 improved translucency and influenced the color to a yellowish to yellow-brownish shade close to Thais' teeth.